Crosstalk of cardiomyocytes and fibroblasts in co-cultures. Issue 6 (June 2015) - Rother, J.; Richter, C.; Turco, L.; Knoch, F.; Mey, I.; Luther, S.; Janshoff, A.; Bodenschatz, E.; Tarantola, M.
Abstract : Electromechanical function of cardiac muscle depends critically on the crosstalk of myocytes with non-myocytes. Upon cardiac fibrosis, fibroblasts translocate into infarcted necrotic tissue and alter their communication capabilities. In the present in vitro study, we determined a multiple parameter space relevant for fibrotic cardiac tissue development comprising the following essential processes: (i) adhesion to substrates with varying elasticity, (ii) dynamics of contractile function, and (iii) electromechanical connectivity. By combining electric cell-substrate impedance sensing (ECIS) with conventional optical microscopy, we could measure the impact of fibroblast–cardiomyocyte ratio on the aforementioned parameters in a non-invasive fashion. Adhesion to electrodes was quantified via spreading rates derived from impedance changes, period analysis allowed us to measure contraction dynamics and modulations of the barrier resistance served as a measure of connectivity. In summary, we claim that: (i) a preferred window for substrate elasticity around 7 kPa for low fibroblast content exists, which is shifted to stiffer substrates with increasing fibroblast fractions. (ii) Beat frequency decreases nonlinearly with increasing fraction of fibroblasts, while (iii) the intercellular resistance increases with a maximal functional connectivity at 75% fibroblasts. For the first time, cardiac cell–cell junction density-dependent connectivity in co-cultures of cardiomyocytes and fibroblasts was quantified using ECIS.